Why do final-year student teachers skip classes? A Chinese perspective. Issue 1 (2nd January 2019) - Yan, Chunmei; He, Chuanjun
Abstract: The lack of deep engagement in academic studies is strikingly noteworthy in current higher education; however, the problem of absenteeism has not yet received sufficient attention in the field of teacher education globally, in particular in the field of EFL (English as a Foreign Language) teacher education at tertiary education level. The reasons for student absenteeism have been left unattended, which may cause the underlying crucial issues to be overlooked. Therefore, this longitudinal study investigated a cohort of 300 final-year Chinese EFL student teachers' perceptions for their reasons for skipping classes. Questionnaires, semi-structured group interviews and class observations were employed complementarily to gather data. The main reasons for absenteeism are students' obsession with employment, a series of curricular and pedagogical shortcomings and students' limited self-discipline and management. Programme-wide support is necessary to address final-year student teachers' concerns about employment prospects, and, most importantly, enhance their learning motivation and self-regulation abilities.